2021
DOI: 10.1002/cyto.a.24484
|View full text |Cite
|
Sign up to set email alerts
|

Further comments on the role of ACE‐2 positive macrophages in human lung

Abstract: The ACE2 expression on the surface of macrophages have been wellestablished by studies such as ACE2 on alveolar macrophages [2-6], blood monocyte-derived macrophages [7][8][9], and macrophages of atherosclerotic carotid arteries [10]. Specifically, the ACE2 protein expression on alveolar macrophages has been demonstrated by different studies with lung tissues from normal human and COVID-19 patients (Table 1). Recently, Wang et al. demonstrated that alveolar macrophages derived from COVID-19 patients displayed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…While it was discovered that there is little to no expression of ACE-2 on most human peripheral blood immune cells it was also found that ACE-2 is highly expressed on tissue macrophages ( 21 , 22 ) including alveolar macrophages, and macrophages of arteries ( 21 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…While it was discovered that there is little to no expression of ACE-2 on most human peripheral blood immune cells it was also found that ACE-2 is highly expressed on tissue macrophages ( 21 , 22 ) including alveolar macrophages, and macrophages of arteries ( 21 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages and myeloid lineage cells are not the primary targets of SARS-CoV-2 infection. However, ACE2 expression on alveolar and blood-derived macrophages is well established in patients during SARS-CoV-2 infection [ 58 , 59 ]. As shown in a recently established system comprising primary and cultured macrophages, expression of ACE2 supports productive viral infection and proinflammatory cytokine responses that may shape the outcome of infection [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…This process may help virus clearance and further spread. In contrast, some other studies have demonstrated a higher level of ACE2 expression in primary human alveolar macrophages and suggest that alveolar macrophages can be directly targeted by SARS-CoV-2 virus [ 52 , 53 ]. However, a lower level of ACE2 expression is reported in M2 alveolar macrophages compared to M1 [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, some other studies have demonstrated a higher level of ACE2 expression in primary human alveolar macrophages and suggest that alveolar macrophages can be directly targeted by SARS-CoV-2 virus [ 52 , 53 ]. However, a lower level of ACE2 expression is reported in M2 alveolar macrophages compared to M1 [ 52 ]. Therefore, phenotypic skewing of alveolar macrophages towards M2 may reduce the self-susceptibility to the virus due to its lower ACE2 expression and also may protect epithelial cells from virus through efficient phagocytosis.…”
Section: Introductionmentioning
confidence: 99%